Glacial isostatic adjustment associated with the Barents Sea ice sheet: A modelling inter-comparison. (1st September 2016) - Auriac, A.; Whitehouse, P.L.; Bentley, M.J.; Patton, H.; Lloyd, J.M.; Hubbard, A.
Abstract: The 3D geometrical evolution of the Barents Sea Ice Sheet (BSIS), particularly during its late-glacial retreat phase, remains largely ambiguous due to the paucity of direct marine- and terrestrial-based evidence constraining its horizontal and vertical extent and chronology. One way of validating the numerous BSIS reconstructions previously proposed is to collate and apply them under a wide range of Earth models and to compare prognostic (isostatic) output through time with known relative sea-level (RSL) data. Here we compare six contrasting BSIS load scenarios via a spherical Earth system model and derive a best-fit, χ 2 parameter using RSL data from the four main terrestrial regions within the domain: Svalbard, Franz Josef Land, Novaya Zemlya and northern Norway. Poor χ 2 values allow two load scenarios to be dismissed, leaving four that agree well with RSL observations. The remaining four scenarios optimally fit the RSL data when combined with Earth models that have an upper mantle viscosity of 0.2–2 × 10 21 Pa s, while there is less sensitivity to the lithosphere thickness (ranging from 71 to 120 km) and lower mantle viscosity (spanning 1–50 × 10 21 Pa s). GPS observations are also compared with predictions of present-day uplift across the Barents Sea. Key locations where relative sea-level and GPS data would prove critical in constraining future ice-sheet modelling efforts are also identified. Highlights: A spherical Earth isostatic adjustment model is applied to the Barents Sea region. Relative sea-level change is reconstructed under six paleo-ice loading scenarios. A database of relative sea-level observations is used to validate model predictions. The best-fit ice load history and Earth rheology is determined across the region. Key areas are identified to optimally constrain future ice-sheet reconstruction.